PENGARUH KUALITAS LAYANAN ADMINISTRASI, KEUANGAN, DAN PERPUSTAKAAN TERHADAP KEPUASAN MAHASISWA STIE TUAH NEGERI - Rispa Eliza; Nasrullah Nasrullah; Meri Yanti; Indah Maha Sari (Jurnal Daya Saing, 2026)
This study aims to analyze the effect of administrative, financial, and library service quality on student satisfaction at Sekolah Tinggi Ilmu Ekonomi (STIE) Tuah Negeri. A quantitative approach with an associative causal design was applied to 114 active students selected through non-probability (accidental) sampling. Data were collected via a five-point Likert scale questionnaire and analyzed using multiple linear regression. Results show that: (1) administrative service quality has a positive and significant partial effect on student satisfaction (Beta = 0,253; sig = 0,001); (2) financial service quality has a positive and significant partial effect on student satisfaction (Beta = 0,371; sig = 0,000); (3) library service quality has a positive and significant partial effect on student satisfaction (Beta = 0,347; sig = 0,000); and (4) simultaneously, the three variables significantly influence student satisfaction (F = 215,800; sig = 0,000) contributing 85,5%. These findings confirm the strategic importance of integrated service quality management for higher education institutions.